The Ego Defense Mechanism of the Main Character in the Novel “Sekosong Jiwa Kadaver” by Ita Fajria Tamim (Literary Psychology Study) - Manjagati, Dea; Raras Hafiidha Sari (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
Literature is the result of the writer's imagination based on his personal experience and background. This research focuses on analyzing the ego defense mechanism of the main character in the novel Sekosong Jiwa Kadaver by Ita Fajria Tamim. This research uses a literary psychology approach with Sigmund Freud's psychoanalytic theory. This study used descriptive qualitative method. The data collection stages in this research included intensive reading, note-taking, and marking the novel. The results of the research conducted show that there are four ego defense mechanisms for the main character Rayya in the novel Sekosong Jiwa Kadaver by Ita Fajria Tamim, including, firstly, diversion which is one way to protect the ego and divert emotions and aggression to things that are considered safer. . Second, repression is an attitude shown by a person to reduce anxiety by suppressing unconscious impulses or desires. The third rationalization is to reduce feelings of disappointment when someone feels like they have failed. Fourth, aggression occurs when someone experiences frustration but cannot express it because it is unclear or does not know where to attack.